Development and characterization of narsoplimab, a selective MASP-2 inhibitor, for the treatment of lectin-pathway–mediated disorders - Dudler, Thomas; Yaseen, Sadam; Cummings, W. Jason (Frontiers in Immunology, 2023)
Overactivation of the lectin pathway of complement plays a pathogenic role in a broad range of immune-mediated and inflammatory disorders; mannan-binding lectin-associated serine protease-2 (MASP-2) is the key effector enzyme of the lectin pathway. We developed a fully human monoclonal antibody, narsoplimab, to bind to MASP-2 and specifically inhibit lectin pathway activation. Herein, we describe the preclinical characterization of narsoplimab that supports its evaluation in clinical trials. ELISA binding studies demonstrated that narsoplimab interacted with both zymogen and enzymatically active forms of human MASP-2 with high affinity (KD = 0.062 and 0.089 nM, respectively) and a selectivity ratio of >5,000-fold relative to closely related serine proteases C1r, C1s, MASP-1, and MASP-3. Interaction studies using surface plasmon resonance and ELISA demonstrated approximately 100-fold greater binding affinity for intact narsoplimab compared to a monovalent antigen binding fragment, suggesting an important contribution of functional bivalency to high-affinity binding. In functional assays conducted in dilute serum under pathway-specific assay conditions, narsoplimab selectively inhibited lectin pathway-dependent activation of C5b-9 with high potency (IC50 ~ 1 nM) but had no observable effect on classical pathway or alternative pathway activity at concentrations up to 500 nM. In functional assays conducted in 90% serum, narsoplimab inhibited lectin pathway activation in human serum with high potency (IC50 ~ 3.4 nM) whereas its potency in cynomolgus monkey serum was approximately 10-fold lower (IC50 ~ 33 nM). Following single dose intravenous administration to cynomolgus monkeys, narsoplimab exposure increased in an approximately dose-proportional manner. Clear dose-dependent pharmacodynamic responses were observed at doses >1.5 mg/kg, as evidenced by a reduction in lectin pathway activity assessed ex vivo that increased in magnitude and duration with increasing dose. Analysis of pharmacokinetic and pharmacodynamic data revealed a well-defined concentration-effect relationship with an ex vivo EC50 value of approximately 6.1 μg/mL, which was comparable to the in vitro functional potency (IC50 33 nM; ~ 5 μg/mL). Based on these results, narsoplimab has been evaluated in clinical trials for the treatment of conditions associated with inappropriate lectin pathway activation, such as hematopoietic stem cell transplantation-associated thrombotic microangiopathy.